PENGARUH ASIMETRI INFORMASI, KAPASITAS INDIVIDU, KOMITMEN ORGANISASI, DAN LOCUS OF CONTROL TERHADAP BUDGETARY SLACK PADA PT. SARIPATI ABADI - Shelfi Malindha; Shita Tiara (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2022)
Abstract This study aims to determine whether there is an effect of information asymmetry, individual capacity, organizational commitment and locus of control on budgetary slack either simultaneously or partially at PT. Saripati Abadi. The research method in this thesis is using quantitative research, with a total sample of 58 consisting of of 2 managers, 7 staff, and production employees consisting of 49 people at PT. Saripati Abadi. The type of data used is primary data. Hypothesis testing in this study uses simple linear regression, F test and t test. The results showed that simultaneously information asymmetry, individual capacity, organizational commitment, locus of control had a significant effect on budgetary slack at PT. Saripati Abadi. In regression, the variables of information asymmetry, individual capacity, organizational commitment, and locus of control have a positive and significant effect on budgetary slack at PT. Saripati Abadi.